Replication of classical infectious bursal disease virus in the chicken embryo related cell line - Cardoso, T. C.; Rahal, Paula [UNESP]; Pilz, D.; Teixeira, MCB; Arns, C. W. (Carfax Publishing, 2000)
Infectious bursal disease (IBD) is an acute, highly contagious viral disease. The diagnosis of IBD depends on time-consuming and costly procedures, like virus isolation on chick embryos and histopathological examination, A double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA), immunoperoxidase and reverse transcription polymerase chain reaction (RT-PCR) were applied in this study to detect classical IBD virus (IBDV) after three blind passages of the Lukert strain on chicken embryo related (CER) cell monolayer after different periods of infection: 6, 12, 24 and 48 h, Cytophatic effects were most evident 12 h post-infection (p.i.) but were observed at 6 h p.i. The maximum discrimination between IBDV-infected and uninfected cell suspensions obtained by the use of DAS-ELISA for virus detection corresponded to 0.597+/-0.02 and 0.010+/-0.01 after 12h p.i., respectively. The RT-PCR was performed using the set of primers A3.1 and A3.2 to amplify the VP2 region of the IBDV genome, This molecular technique demonstrated that from 6 h p.i., it was possible to detect the viral RNA. The results show that the CER cell line can be used for classical IBDV propagation, confirmed by the DAS-ELISA, immunoperoxidase and RT-PCR assay.